Imposição de mãos : um estudo de religiões comparadas. - Teixeira, Francisca Niédja Barros (2009)
This study aims to make a comparative analysis of the blessing therapeutic-relogious technique, by hands imposition in three philosofical religious entities, trying to discover their contextual distinction and the possible estructures of this phenomenon. They have been used as sources, besides the regarded bibliograghy,as well as interviews of those who adapt the tradition that they have been using as a prayer. Historically, they are situated and contextualized in the common oriental tradition present in brazilian derivation, the practice of Passe in the Spiritism, Johrei of Messianic Church and Reiki in the movement using the same name. Soon afeter, by the comparative analysis of the testimonies of the participantes, it will be outlined a morfology of the sacret that is showed in the terapeutical experiences of Hands Imposition, Which make variations between healt and salvation.